Characteristics of Hantaviruses as Causative Agents of the Zoonotic Hemorrhagic Fevers - A. A. Ishmukhametov; T. K. Dzagurova; V. G. Morozov; C. C. Kurashova; M. V. Balovneva; C. E. Sotskova; E. A. Tkachenko (Эпидемиология и вакцинопрофилактика, 2017)
Hemorrhagic fever with renal syndrome (HFRS) has been a major concern for public health in different countries of the Euroasian continent for decades. In 1970s the disease was associated with newly discovered viruses that were to become new members (under the genus Hantavirus) of the family Bunyaviridae. During a deadly outbreak of pulmonary syndrome in the southwestern United States in 1993, it was shown that causative agents of this devastating disease (designated hantavirus cardio-pulmonary syndrome, HCPS) were also hantaviruses. By now hantaviruses are found worldwide and associated with different species of the order Rodentia , which are their natural carriers. Hantaviruses persistently infect rodents, however do not cause any disease in them and are transmitted to humans through aerosolized excreta. For a long time studies of hantaviruses were limited by their high pathogenicity, absence of animal model of infection, and poor growth in cell cultures. With the rapid development of molecular biological techniques in last several years substantial progress has been made in various fields of hantavirus research. Different aspects of hantavirus ecology, molecular biology, morphology and pathogenesis, as well as current diagnostic methods and other characteristics of hantaviruses are considered in this review.